2018
DOI: 10.1177/2048872618764418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of coronary microvascular dysfunction among chest pain patients in the emergency department

Abstract: Despite their low-risk profile, nearly one half of symptomatic and mostly obese emergency department patients without evidence of myocardial infarction or coronary artery disease had CMD. The results could explain the high rates of return visits associated with chest pain, although their application to the general emergency department population require validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…Although sex differences in resting MBF and CFR have been observed in invasive CRT [3,17,57], only one of the included studies included assessed sex differences regarding CBF and reported no signi cant sex differences [30]. These ndings are consistent with another study comparing non-invasive CFR between men and women using PET [58]. Therefore, further research is needed to establish whether or not sex-speci c cut-off values are required for the non-invasive diagnosis of CMD.…”
Section: Sex Differencesmentioning
confidence: 57%
“…Although sex differences in resting MBF and CFR have been observed in invasive CRT [3,17,57], only one of the included studies included assessed sex differences regarding CBF and reported no signi cant sex differences [30]. These ndings are consistent with another study comparing non-invasive CFR between men and women using PET [58]. Therefore, further research is needed to establish whether or not sex-speci c cut-off values are required for the non-invasive diagnosis of CMD.…”
Section: Sex Differencesmentioning
confidence: 57%
“…A full description of patient flow in the chest pain center has been described previously. 15 Briefly, all patients presented with chest pain and underwent a standard protocol to rule out ACS with serial cardiac enzymes and electrocardiograms at 0, 3 and 6 hours before imaging (see Appendix Figure). Consenting patients provided blood samples between 7 and 11am prior to PET/CT, after an overnight rest and within 24 of hours of the chest pain symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Full protocol is described elsewhere. 15 Attenuation corrected PET images were first evaluated visually for regional perfusion defects. Regional and global quantitative flow was determined using a commercial software package, Corridor 4DM v2013 (INVIA Medical Imaging Solutions, Inc.) that employs a previously validated generalized factor analysis of dynamic sequences (GFADS).…”
Section: Methodsmentioning
confidence: 99%
“…Microvascular dysfunction has been identified as an important cause of ischaemia in cardiovascular disease. Coronary microvascular dysfunction (CMD) is quite common in non-obstructive coronary artery disease and affects patients' life quality (Safdar et al 2020). However, there is still no effective therapy for CMD.…”
Section: Introductionmentioning
confidence: 99%